Palaeomagnetic Studies in the British Caledonides-VI Regional and Global Implications - Briden, J. C.; Morris, W. A.; Piper, J. D. A. (Geophysical Journal International, 1973)
Palaeozoic palaeomagnetic data from the British Isles are reviewed and are found to be consistent with erratic polar shift from the vicinity of 10° N, 180° E in the Ordovician to 0°, 145° E in the Siluro-Devonian and to 25° N, 160° E in the early Carboniferous. The Cambrian pole is less well established near 25° N, 170° E. The rates and times of shifts are discussed. World-wide palaeomagnetic data suggest the existence of three groups of continents in the Early and Middle Palaeozoic—the Gondwanan, Euramerican and Siberian groups—separated by large oceans which closed in the Late Palaeozoic along the lines of the Hercynides and Uralides. The data from Gondwana and Siberia are internally consistent and each may have been a single plate to which only peripheral slices were added subsequently. Data from Euramerica are less coherent. The most probable explanation seems to be that this group of continents was loosely-knit and consisted of the North American and the Baltic/Russian plates (which joined in the Silurian on the site of the Scandinavian Caledonides) and the British Isles sub-plate which joined in the Devonian (on previously unrecognized sutures lying in the present North Atlantic and North Sea respectively). This interpretation takes all the data at face value and assumes that time-coverage is adequate in all parts of the region. Alternatively, if time-coverage was not adequate, Britain might have been part of the North American plate, but further work is required to discriminate between these interpretations. Palaeomagnetic evidence from the British Isles also indicates that little or no closure has taken place across the British Caledonides since Early Ordovician time. If so the British Isles sub-plate may have been rotated in azimuth as well as being transported laterally before joining the Euramerican plate. Examples of rotation and remagnetization on a more local scale are cited, and are ascribed to tectonic and thermal effects of orogeny respectively. The Euramerica and Gondwana groups were already ...